(3GdQhV GdGfa aj TQM ZQjH GdSjQs - (3CHh GdbSe YHO GdQMef Hf YHO Gddg Hf CMeO Hf CHi GdMSf GdNKYei Ke GdSgjdis; (3YHO Gdedc Hf gTGe Hf CjhH GdMejQj GdeYGaQj, CHh eMeO, LeGd GdOjf,J (B213 (3g` s
(3ChdgG (B:s
(3MeOkG ddg ebOe Ydi cd GeQ Pi HGd (B,(3HYO aEfi GfJMjJ ai gPG GdGedG HYO GSJNGQI Edi GjVGM eG hbY ai SjQI QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3BNQ GdehLhO efg bjd cja LGR dg Cf jfXQ Edi POjgG abO Qhi ai Pdc CfgG s
(3HgG fXGe GdJYbjHIs
(3SjQI QShd Gddg Udi Gddg Ydjg hSde dGHhHcQ eMeO Hf GSMGb GdeWdHis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B166 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B192s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs